Dorsal Raphe Nucleus Serotoninergic Neurons Mediate Morphine Rewarding Effect and Conditioned Place Preference. (1st January 2022) - Fu, Bo; Yao, Jun-qi; Lu, Chang; Wang, Bin; Li, Zeqi; Huang, Ming; Tian, Tian; Peng, Hui; Liu, Shao-jun
Highlights: Morphine activate the 5-HT neurons. Optogenetic activate 5-HT neurons encode reward. Optogenetic inhibit 5-HT neurons reverse morphine CPP. Abstract: Morphine rewarding properties are the main reasons for drug-craving in behaviors occurring during morphine addiction. It has been suggested that morphine addiction relies on signals to the mesolimbic dopamine system, although the mechanisms outside the dopaminergic system are still unclear. Notably, the role of the dorsal raphe nucleus (DRN) serotoninergic (5-hydroxytryptamine, 5-HT) system remains unexplored. Using in vivo electrophysiological and optogenetic approaches, we found that morphine treatment increased DRN 5-TH neurons firing rate and optogenetic activation of DRN 5-HT neurons induced a rewarding effect, indicating that morphine reward is related to DRN 5-HT neurons. Accordingly, optogenetic inhibition of DRN 5-HT neurons following morphine injection reversed conditioned place preference (CPP) during chronic morphine treatment. These findings aid our understanding of the new functions of the DRN 5-HT neurons for morphine rewarding effect and provide a potential approach for the treatment of morphine addiction.